Herbal tea, a novel adjuvant therapy for treating type 2 diabetes mellitus: A review - Zhang, Xiangyuan; Zhang, Lili; Zhang, Boxun; Liu, Ke; Sun, Jun; Li, Qingwei; Zhao, Linhua (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a metabolic, endocrine disease characterized by persistent hyperglycemia. Several studies have shown that herbal tea improves glucose metabolism disorders in patients with T2DM. This study summarizes the published randomized controlled trials (RCTs) on herbal tea as a adjuvant therapy for treating T2DM and found that herbal teas have potential add-on effects in lowering blood glucose levels. In addition, we discussed the polyphenol contents in common herbal teas and their possible adverse effects. To better guide the application of herbal teas, we further summarized the hypoglycemic mechanisms of common herbal teas, which mainly involve: a) improving insulin resistance, b) protecting islet β-cells, c) anti-inflammation and anti-oxidation, d) inhibition of glucose absorption, and e) suppression of gluconeogenesis. In conclusion, herbal tea, as a novel adjuvant therapy for treating T2DM, has the potential for further in-depth research and product development.